Hydroelectric Power Auto with Torque Peripheral to the Wheels (Global Journal of Human-Social Science, 2016)
The current state of the art of means of transport was affected by heat engines which predominated for the absence of viable renewable energy with small dimensions But the invention of the pump with double separate supply until the impeller has allowed the pressurized hydropower invention with recycling water which can replace thermal engines Certainly it is more cumbersome but immensely cheaper and nonpolluting From the point of view of the electro-mechanical means of transport that will use the pressurized hydropower are simplified eliminating in addition to heat engines the fuel tank the mufflers and exhaust pipes the engine cooling system the transmission shafts the exchange gears clutch differential The hydroelectricelectronic system which will be used does not need of fuels and even of heavy and expensive batteries lithium accumulators with little shipping autonomy which involve considerable disposal costs and the use of materials in the process of exhaustion The hydroelectric means of transport will cost less of the existing means of transport for the absence of many of the components mentioned above but also because the motion transmission by electric-electronic means is much more economical than the mechanical without sacrificing the safety on the road In fact the fourwheel drive of the wheels may be of series and all the wheels powered and controlled individually Also the control of the differential speed in the curves and the braking system ABS may be incorporated in the motors that turn the wheels by transmitting the driving torque to the periphery and not in the center of the wheels as in the existing vehicles